Technology Improvement and Micro, Small, and Medium Enterprises (MSMEs) on Regional Development in Special Region of Yogyakarta - Rian Marita Sugiarto; Doddy Aditya Iskandar (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
A new perspective on regional economic development is development capital generated from the region. MSMEs and Higher Education as development capital of the Special Region of Yogyakarta (DIY) have different characteristics. Development is recognized as a process in which interrelationships and effects between the variables lead to regional development. Therefore, it is necessary to identify the effect of regional development capital on regional development. This study aims to examine the use of PLS-SEM in designing a model of the relationship between technological innovation, capital, and workforce on regional development. This current study also aims to observe the effect of latent predictor variables (Xi) of technology, innovation, capital, and workforce on LPE, HDI, and poverty rate as the latent dependent variable of regional development (Yi). Regional development capital has a positive effect on LPE. Technology has a positive and significant effect on innovation by 92.6%. Innovation Technology positively affects Economic Growth by 14.44% but is not significant. Though it is not significant, regional capital proxied by MSMEs positively affects economic growth. The workforce has a negative and insignificant effect on the economic growth of -28.3%. LPE and HDI have a negative effect on the poverty rate, although not significant at -6.8% and -13.3%, respectively. LPE and HDI play a role in reducing poverty. However, they perform on different paths. Workforce productivity is still low. Thus, it has not been able to boost economic growth and reduce poverty. These results are expected to be utilized as a basis for developing strategies for technology utilization by MSMEs